Analisis Faktor Hambatan dalam Pelayanan di Unit Pendaftaran Rawat Jalan Terkait Metode 2M (Man dan Machine) di Puskesmas Botania - Mulyana, Mulyana; Situmorang, Masriani; Monadia, Monadia (Transpublika Publisher, 2025)
This activity aims to analyze the inhibiting factors affecting outpatient registration services at Puskesmas Botania Batam, focusing on the 2M approach (Man and Machine). Observations revealed significant barriers impacting service quality, such as changes in staff scheduling, miscommunication among staff, and equipment malfunctions involving computers and queue machines. The methods used were direct observation and interviews with registration officers during field practice. Based on the findings, it is recommended to improve staff coordination and conduct regular maintenance of facilities and infrastructure to enhance service quality.